Socio-cultural Aspects of Pregnancy Health in Indonesia: Literature Review: Aspek Sosial Budaya Kesehatan Kehamilan di Indonesia : Literatur Review - Arwiyantasari, Wida Rahma; Rury Narulita Sari; Widya Lusi Arisona; Kiky Anggun Sanjaya (Jurnal Midwifery, 2024)
Every country, especially Indonesia, has a diverse culture, especially the socio-cultural aspects of pregnancy health. The results of health ethnographic research conducted in 2012 in 12 ethnicities in Indonesia show that health culture affects maternal and child health problems that are very concerning, one of which is during pregnancy. This study uses secondary data, namely collecting national literature through the Google Scholar database. There are 5 representative literature according to the topic, namely the socio-cultural aspects of pregnancy from various tribes in Indonesia (Java, Dayak, Baduy, and Kampung Pulau Seberang). It can be concluded that traditions from the socio-cultural aspect are very influential in pregnancy health practices, where some pregnant women still carry out the culture, especially in coastal and rural areas that are thick with traditional customs.